Absolute standardization of 57Co and analysis of the results obtained in two international comparisons. (October 2018) - Sahagia, Maria; Luca, Aurelian; Antohe, Andrei; Ioan, Mihail-Razvan
Abstract: The absolute standardization of Co-57 by the 4π(PC)-γ coincidence method, in efficiency extrapolation variant, is presented. An original, improved method, based on the use of the equivalent decay scheme, was applied; apart from the enhancement of efficiency, a diminution of extrapolation slope was obtained, lowering the extrapolation uncertainty. The results obtained in the participation at the supplementary comparison CCRI(II)-S6.Co-57 and at the key comparison code BIPM.RI(II)-K1.Co-57 are presented. The method allows to simplify the treatment of 56 Co and 58 Co impurities' correction, which influences significantly the measurements in a CENTRONIC type ionization chamber. An example of treatment of this mixture, where the influence of impurities on results was analyzed, will be presented. Highlights: A solution of 57 Co was standardized absolutely by the 4π(PC)-γ coincidence method. The results of CCRI(II)-S6. Co-57 and BIPM.RI(II)-K1. Co-57 comparisons were contradictory. This paper explains these differences, by the contribution of 58 Co and 56 Co impurities.